The Structure of Theatrical Performance And Ontological Debate In Iraqi Theatrical Performance (Using The Play " Disagreement " As A Model)?) (Journal of the College of Basic Education, 2026)
The current research examines the structure of theatrical performance from an ontological perspective, considering it an aesthetic and philosophical framework. It explores the problematic nature of human existence within the discourse of theatrical performance.The research establishes its relationship to social and intellectual realities, class conflict, and religious ideologies—particularly extremism.It begins with the premise that contemporary realistic theatrical performance does not merely imitate or superficially represent reality, but rather transforms into an ontological and existential act and debate that reveals the fragmented self within the social, intellectual, and cultural environment. The research seeks to analyze the outputs of the performance as a structural and dialectical product of the text, the performance, and the reception, critically reproducing reality.The research comprises four chapters:Chapter One: Methodological Framework: This chapter includes the research problem, which is the following question: (What is the structure of theatrical performance and ontological debate in Iraqi theatrical performance (using the play " Disagreement " as a model)?)It also includes the research objective: (To identify the dimensions of the structure of theatrical performance and ontological debate in contemporary Iraqi theatrical performance, using the play " Disagreement " as a model).The importance of the research lies in highlighting the revelation of the structure of theatrical performance based on the ontological dialectical approach in contemporary Iraqi theatrical performance, which benefits researchers and practitioners in the field of theater. The research scope is defined as: temporally (2021), geographically (Baghdad, Iraq / Al-Rasheed Theater), and thematically (a study of the structure of theatrical performance and ontological debate in Iraqi theatrical performance). Finally, some terms mentioned in the research title are defined.Chapter Two includes three sections:Section One: The Structure and Development of Acting PerformanceSection Two: Performance in International ExperiencesSection Three: The Ontological Debate on PerformanceThe chapter then presented the most important indicators resulting from the theoretical framework. Chapter Three includes the research procedures, the research population, and the research methodology.The researcher used the descriptive method and the research instrument, and then the research sample (Disagreement), which was intentionally selected to represent the research objective and to identify the structure of the theatrical performance and the ontological debate in the play (Disagreement).The researcher used this play as a model to arrive at results that align with the research problem and its objective.Chapter Four presents the research findings, conclusions, recommendations, and suggestions.Among the most important findings are:The performance transformed and formed a structural and semantic presence in the play "Disagreement" revealing the class structure and the social and intellectual backgrounds of the right and left. The ontological dialectic was embodied through the characters' conflict, manifested in their actions, behavioral patterns, and intellectual and religious beliefs. This gave the performance and presentation a critical and dialectical dimension, influencing the structure of the performance and its reception.The structure of the acting performance revealed and reinforced the philosophy of the text and the performance. The ontological dialectic was manifested through the revelation of the fragmented individual living with conflicting affiliations (religious, class-based, and ideological). The performance produced a series of structural transformations, as the actors' performances contributed to highlighting the individual's loss of a center of existence and a stable sense of identity.The most important conclusions are:Theatrical performance and its structural patterns represent an ontological dialectic, as performance is not limited to its construction and effectiveness in the theatrical presentation; it is an act of existential dialectic that reveals philosophical, psychological, and intellectual dimensions.2. Theatrical characters in contemporary theater act upon and embody human emotions concerning existence, freedom, and identity. This, in turn, grants the performance philosophical and ethical dimensions, as theatrical performance transcends the boundaries of familiar and traditional acting. The research concludes with a list of the most important sources and references cited within the text.